2022
DOI: 10.22207/jpam.16.3.34
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Bacteria and Yeasts Isolated from the Milk of Dairy Cattle Presenting with Subclinical Mastitis in Puebla, Mexico

Abstract: This study was designed to identify the bacteria and yeasts from the milk samples of dairy cattle presenting with subclinical mastitis and evaluate their antimicrobial susceptibility. We collected a total of 52 milk samples from cows across three farms in San Salvador El Seco (Puebla, Mexico). Microbial isolation was performed using microbiological techniques followed by taxonomic identification of bacteria and yeasts. Antimicrobial susceptibility was evaluated using the guidelines provided by the Clinical Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The yeast species was identified by morphological and biochemical growth tests. Toxqui-Munguia et al (2022) reported the isolation of Y. lipolytica from cows with subclinical mastitis in Mexico. Additionally, the species identification was identified by morphological and biochemical growth.…”
Section: Yarrowia Lipolyticamentioning
confidence: 99%
“…The yeast species was identified by morphological and biochemical growth tests. Toxqui-Munguia et al (2022) reported the isolation of Y. lipolytica from cows with subclinical mastitis in Mexico. Additionally, the species identification was identified by morphological and biochemical growth.…”
Section: Yarrowia Lipolyticamentioning
confidence: 99%